2020
DOI: 10.1039/c9gc01537j
|View full text |Cite
|
Sign up to set email alerts
|

Why we might be misusing process mass intensity (PMI) and a methodology to apply it effectively as a discovery level metric

Abstract: Are the comparisons of PMI values fair and informative, are you making a like versus like assessment?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…The same conclusions, revealed from simulations of other reaction types (amide synthesis, Mitsunobu reaction), support the general applicability of these guidelines beyond thiosulfonate synthesis …”
Section: Assessing the Green Credentialssupporting
confidence: 72%
“…The same conclusions, revealed from simulations of other reaction types (amide synthesis, Mitsunobu reaction), support the general applicability of these guidelines beyond thiosulfonate synthesis …”
Section: Assessing the Green Credentialssupporting
confidence: 72%
“…Nowadays, transformations are evaluated numerically using parameters such as atom economy , E factor , process mass intensity , and many others. 6 − 17 More recently, enormous efforts have been made to develop the science of “lifecycle assessment”—the quantitative metrics by which the total mass and energy inputs and waste outputs of a given chemical transformation are evaluated for their environmental impact. 18 21 Since then, industrial chemists have led the charge by compiling important guides on reagent and solvent selection.…”
Section: Introductionmentioning
confidence: 99%
“…Under the standard flow conditions shown in Table 2, the desired product 2 was constantly obtained in 91–94% yields. No deactivation was observed after continuous reaction for 120 h. The overall reaction economy was assessed by evaluating the process mass intensity (PMI), [11] which confirmed the advantages of using heterogeneous catalysts; the trifluoroethanol solvent could also be reused in the flow system (Table 2). Indeed, recycling experiments, carried out using recovered trifluoroethanol and reusing the catalyst‐packed reactor with the same contents, confirmed that consistently high yields were achieved for four runs.…”
Section: Methodsmentioning
confidence: 73%